OP0084 Rescue from the failing heart in systemic sclerosis, a novel insight: targeting TGF-β/FRA2-dependent autophagy. (15th June 2017) - Stellato, M; Rudnik, M; Renoux, F; Pachera, E; Kayalar, D; Sotlar, K; Klingel, K; Henes, J; Blyszczuk, P; Distler, O; Kania, G
Abstract : Background: The majority of Systemic Sclerosis (SSc) patients have subclinical primary cardiac involvement, which resembles the inflammatory dilated cardiomyopathy (iDCM) with inflammation and fibrosis. Firstly, cellular progenitors of pathological myofibroblasts remain undescribed. Secondly, autophagy may favor fibrosis through enhanced differentiation of fibroblasts in myofibroblasts Objectives: To unravel the role of Fos-related antigen 2 (Fra2)/autophagy crosstalk in TGF-β-driven myocardial fibrosis in SSc Methods: Genetically modified mice overexpressing Fra2 were used. Endomyocardial biopsies (EMBs) from SSc/iDCM patients and hearts from Fra2 tg and control mice were analysed by immunohistochemistry (IHC) and immunofluorescence (IF). Murine myocardial gp38 + (podoplanin + ) stromal cells were sorted and stimulated in vitro with TGF-β. The cellular phenotype was assessed by qPCR, IF, stress fiber staining, SIRCOL and contraction assay on sorted cells. The antisense oligonucleotide GapmeR was used to knock-down Fra2 Results: The myocardium of SSc/iDCM patients (n=10) showed the typical phenotype of iDCM: increased fibrotic area with extended collagen deposition and enlarged number of pathological myofibroblasts, expressing Fra2 and, interestingly, the autophagy markers LC3B and Atg5. Similarly, Fra2 tg mice showed higher expression of profibrotic markers: αSMA, vimentin and collagen I compared to control mice (n=5), as well as the expression of the autophagy markers LC3B and Beclin in fibrotic regions. Among cardiac stromal cells (Ter119 - CD45 - CD31 - Sca1 + CD29 + ) the frequency of gp38 + cells was significantly higher in Fra2 myocardium compared to control mice. The majority of gp38 + cells co-expressed αSMA, vimentin and collagen I together with autophagy markers (LC3B and Beclin, n=3). Following in vitro stimulation with TGF-β, gp38 + cells entered fibroblast-to-myofibroblast transition characterized by increased mRNA and protein levels of αSMA, collagen I, fibronectin (n=3–6), αSMA-fiber and stress-fiber formation (n=3), increased cell proliferation (n=4; p=0.04) and contraction capability (n=2; p<0.05) and enhanced collagen secretion (n=3; p=0.04). Importantly, Fra2 tg gp38 + cells showed the presence of αSMA and stress fibers even without TGF-β stimulation as well as an increased contraction capability compared to control cells. TGF-β stimulation of control gp38 + cells induced the expression of LC3B, Beclin and Atg5 at mRNA and protein level (n=3–5). In contrast, TGF-β inhibition caused the downregulation of these markers (n=3). In addition, Fra2 silencing resulted in a decreased differentiation capability of gp38 + cells: mRNA and protein levels of the profibrotic genes αSMA and collagen I were significantly downregulated (n=5; p=0.007). Moreover, Fra2 downregulation impaired the secretion of collagens (n=4; p<0.05) and the formation of αSMA fibers (n=3) in addition to a significant downregulation of mRNA and protein expression of LC3B, Beclin and Atg5 (n=3) Conclusions: The TGF-β/Fra2 axis fosters an enhanced autophagy flow, leading in turn to the stromal-to-myofibroblast transition. Therefore, targeting this process might be a therapeutic strategy to abrogate fatal cardiac remodeling in SSc Disclosure of Interest: M. Stellato: None declared, M. Rudnik: None declared, F. Renoux: None declared, E. Pachera: None declared, D. Kayalar: None declared, K. Sotlar: None declared, K. Klingel: None declared, J. Henes: None declared, P. Blyszczuk: None declared, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha, G. Kania Grant/research support from: Bayer AG